Employee Engagement in the Emergency Department at Rumah Sakit Umum Daerah K in Jakarta: A Case Study - Listyani, Nadya Kaulika; Tan, Jacob Donald (Jurnal Economic Resource, 2025)
The emergency department (ED) plays a critical role as the frontline of healthcare systems, serving as the primary entry point for patients who need immediate treatment related to life safety. The quality of care in the EDs not only influences patient satisfaction but also impacts employee engagement. Employee engagement is a multifaceted psychological construct that describes the emotional, cognitive, and behavioral commitment of employees to their job and organization. This study explores the factors influencing employee engagement among ED staff at RSUD K in Jakarta through a qualitative case study approach. Using in-depth semi-structured interviews, direct observations, and field notes, the research identifies key themes including teamwork, administrative workload, access to meals and rest areas, communication with the management, and the extent to which staff aspirations are considered. Findings reveal that strong team work enhances engagement, while lack of managerial support and inadequate facilities negatively impact morale and performance. The study underscores the importance of responsive leadership and supportive work environments in promoting staff engagement in ED.